Comparison between AS5100 fatigue load model and fatigue from representative traffic - Caprani, Colin; Zhou, Ziyi; ICASP14 (My University, 2023)
Bridges provide an irreplaceable role in road transportation, and so it is vital to properly manage them. The traffic loading caused by trucks is decisive in bridge design and assessment, because it not only controls the strength design, but critically also the fatigue life. The current Australian bridge fatigue model in AS5100.2 was mainly developed by Prof. Paul Grundy in 2004. In this model, the bridge fatigue damage caused by each heavy vehicle is quantified as a certain number of 70\%~M1600 load model vehicles. Although this model fulfilled the need at the time, it may not precisely predict the fatigue damage. Thus, this research compares the fatigue damage predicted by code with the fatigue damage caused by representative traffic, using extensive simulations of real traffic scenarios. This paper contributes to the development of the next generation of the AS5100 fatigue load model based on extensive collections of new traffic data.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED